Pyrimidine derivatives impact and development cultivar-differentiators of potato wart in culture in vitro - Stoyanova, K.; Gavrilyuk, A.; Skoreiko, A.; Andriychuk, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To determine the role of pyrimidine derivatives as growth stimulators in microclonal propagation and to study their effect on morphometric parameters and on the micropropagation coefficient of potato wart cultivar-differentiators in vitro culture. Methods. The study was conducted in 2023—2024 at the Laboratory of Biotechnology of Agricultural Crops, Ukrainian Scientific Research Plant Quarantine Station, Institute of Plant Protection of NAAS. Plants were grown in a cultivation room under a 16- hour photoperiod with a light intensity of 2000—2500 lux, temperature of 22—25°C, and air humidity of 60—80%. To optimize the reproduction process and productivity of potatoes in in vitro culture, an experiment was carried out by adding various substances to the Murashige and Skoog (MS) nutrient medium: IAA (1 mg/L) + adenine (0.5 mg/L); IAA (1 mg/L) + adenine (0.5 mg/L) + xymedone (0.1 mL/L); IAA (1 mg/L) + adenine (0.5 mg/L) + xymedone (0.05 mL/L); IAA (1 mg/L) + adenine (0.5 mg/L) + xymedone (0.01 mL/L). The objects of the study were potato wart cultivar-differentiators: the early-maturing ‘Glazurna’ and the medium-late ‘Chervona Ruta’. For each cultivar, 25 plants were cut for propagation, with the experiment repeated three times. Results. The addition of pyrimidine derivative–based preparations to the MS nutrient medium had a positive effect on the regulation of growth and development of potato wart cultivar-differentiators in vitro culture. The most effective treatment for the ontogenesis of test-tube potato plants was the addition of xymedone at a concentration of 0.05 mL/L to the MS nutrient medium. In ‘Glazurna’ plants, plant height increased 1.3-fold and the number of internodes 1.7-fold, while in ‘Chervona Ruta’ plant height increased 1.2-fold and the number of internodes 1.8-fold. Conclusions. The tested preparations promoted an increase in plant height, number of internodes, and micropropagation coefficient. Adenine, as a component of nucleic acids and coenzymes, plays an important role in plant metabolism. It promotes more efficient energy use, affects photosynthesis intensity, cell division, and potato resistance to stress factors. IAA (indole-3-acetic acid) is one of the main natural auxins regulating plant growth and development; it participates in processes of cell division, elongation, differentiation, root formation, and other morphogenetic processes.